Seismic Investigation of Ice Properties and Bedrock Topography at the Confluence of Two Glaciers, Kaskawulsh Glacier, Yukon Territory, Canada - Dewart, Gilbert (Institute of Polar Studies, The Ohio State University., 1968)
The field investigations were carried out as part of the Icefield Ranges Research Project. The purpose of this study is twofold: (1) to investigate seismic velocity inhomogeneity and anisotropy in strongly deformed glacier ice; and (2) to determine the form and dimension of that part of a sub-glacial valley where two large temperate glaciers merge. The field investigations were carried out during the summers of 1964 and 1965 at the confluence of the North and Central Arms of the Kaskawulsh Glacier in the St. Elias Mountains, Yukon Territory, Canada. Results of the fieldwork are discussed in detail. Arctic Institute of North America Explorer's Club of New York U.S. National Science Foundation, Office of Antarctic Programs